Atypical Presentation of Thyrotoxic Periodic Paralysis Without Overt Hyperthyroid Symptoms: A Case Report - I Made Satria Wibawa; I Gede Risnawan Suastika Ardanayasa (Riviera Publishing, 2026)
Thyrotoxic Periodic Paralysis is a rare complication of hyperthyroidism characterised by acute muscle weakness due to hypokalemia. This condition is more commonly reported in Asian populations and may be overlooked when classic symptoms of hyperthyroidism are absent, potentially leading to recurrence and serious complications. A 40-year-old man presented with sudden weakness of all four extremities following consumption of a high-carbohydrate meal. The patient did not exhibit typical symptoms of hyperthyroidism. Laboratory evaluation revealed severe hypokalemia with elevated FT? levels and markedly suppressed TSH. The patient was treated with intravenous and oral potassium replacement, along with methimazole and propranolol. Muscle strength improved within 24 hours and recovered completely by the third day of hospitalisation. Thyrotoxic Periodic Paralysis occurs due to an intracellular shift of potassium mediated by increased Na?/K?-ATPase activity in the setting of thyrotoxicosis. Attacks are often triggered by high-carbohydrate intake or physical exertion. Diagnosis can be challenging in patients without overt hyperthyroid manifestations; therefore, thyroid function testing is essential in cases of acute hypokalaemic paralysis. Management includes careful potassium correction and control of thyrotoxicosis to prevent recurrence. Thyrotoxic Periodic Paralysis should be considered in any patient presenting with acute weakness accompanied by hypokalemia, even in the absence of classic hyperthyroid symptoms. Prompt treatment and adequate control of thyrotoxicosis are associated with favourable clinical outcomes.